Factors of Production and the State: Capital, Labour, Energy. (November 2021) - Musso, Marta
Abstract : Is state intervention making a comeback in economic policy? Should it make a comeback in economic policy? And, if so, what should this intervention look like? The relations between the state and the economy are a recurring theme throughout modern history, at least since the invention of the nation-state, but in Covid Europe these questions have made the news headlines for the first time in decades. This has been in addition to the strains and challenges posed to the global economy by climate change, which have increasingly put state intervention at the forefront of economic policy. In this context, it is not surprising that state intervention has been the subject of many new books. The ones under review here, all published between 2014 and 2020, add new food for thought to the topic. They raise important questions at a time when ideas around the relations between state, entrepreneurship and resources are beginning to be rediscussed, even in the most conservative economic circles.